2013
DOI: 10.1177/0956462412473885
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Alcohol Use Disorders Identification Test (AUDIT) to determine the prevalence of alcohol misuse among HIV-infected individuals

Abstract: The aim of the paper is to evaluate alcohol misuse among an inner city adult HIV clinic population with AUDIT (Alcohol Use Disorders Identification Test). A cross-sectional HIV outpatient clinic analysis between 28 February 2011 and 11 March 2011 was carried out. AUDIT, demographic and clinical data were collected. Univariate analysis was performed to look for the associations between variables. Backward stepwise multivariate analyses were performed on significant variables from the univariate analysis to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…This is consistent with other studiesboth industrial 21,25,26 and community based 22,27,24 . Income Monthly income of the participants was not significant in the multivariate analysis which was consistent with other studies 22,26 .…”
Section: Educationsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with other studiesboth industrial 21,25,26 and community based 22,27,24 . Income Monthly income of the participants was not significant in the multivariate analysis which was consistent with other studies 22,26 .…”
Section: Educationsupporting
confidence: 82%
“…Therefore, there was not much difference in terms of mean age of initiation. In a study 24 done in Dublin, Ireland, it was reported that younger age was more likely to be dependent drinkers. However, the study population was HIV infected individuals which might be reason for the finding.…”
Section: Age Religion and Castementioning
confidence: 99%
“…Reported at risk drinking ranges from 8 to 50 % of PLWH [12, 2426], with our cohort falling around the midpoint. In addition to identifying a large proportion of patients with diagnostic criteria for an AUD using the full AUDIT, we identified an even larger proportion of individuals with potentially hazardous ongoing drinking beyond those with defined AUDs, as evidenced by excessive consumption on the AUDIT-C or AUDIT-3 binge drinking.…”
Section: Discussionmentioning
confidence: 91%
“…41 This scale has been used worldwide both in the general population and in HIV-positive patient samples. 42,43 A total WHO-AUDIT 8 has been shown to discriminate those with and those without problematic drinking conditions. 40 Drug Abuse Screen Test.…”
Section: Measurementsmentioning
confidence: 99%